2023
DOI: 10.4014/jmb.2306.06041
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside Induces UCP1- and ATP-Dependent Thermogenesis in Beige Adipocytes via the Activation of Dopaminergic Receptors

Abstract: Echinacoside (ECH) is a naturally occurring phenylethanoid glycoside, isolated from Echinacea angustifolia , and this study aimed to analyze its effect on thermogenesis and its interaction with dopaminergic receptors 1 and 5 (DRD1 and DRD5) in 3T3-L1 white adipocytes and mice models. We employed RT-PCR, immunoblot, immunofluorescence, a staining method, and an assay kit to determine its impact. ECH showed a substantial increase in browning signals in vitro and a decrease in adipogenic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous studies indicated that the specific knockout of HIF-2α in mice could disturb the intestinal lactic acid level, thereby decreasing the abundance of Bacteroides and increasing that of rumen cocci, which resulted in promoting the levels of taurocholic acid and deoxycholic acid ( Wu et al., 2021 ). These acids could activate the adipose G-protein-coupled bile acid receptor and upregulate the expression of UCP1 and CKMT2 , increasing heat production in white adipose tissue ( Haddish and Yun, 2023 ). Clostridium butyricum CCFM1299 could reduce obesity by increasing energy expenditure and regulating host bile acid metabolism ( Liao et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that the specific knockout of HIF-2α in mice could disturb the intestinal lactic acid level, thereby decreasing the abundance of Bacteroides and increasing that of rumen cocci, which resulted in promoting the levels of taurocholic acid and deoxycholic acid ( Wu et al., 2021 ). These acids could activate the adipose G-protein-coupled bile acid receptor and upregulate the expression of UCP1 and CKMT2 , increasing heat production in white adipose tissue ( Haddish and Yun, 2023 ). Clostridium butyricum CCFM1299 could reduce obesity by increasing energy expenditure and regulating host bile acid metabolism ( Liao et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that the specific knockout of HIF-2a in mice could disturb the intestinal lactic acid level, thereby decreasing the abundance of Bacteroides and increasing that of rumen cocci, which resulted in promoting the levels of taurocholic acid and deoxycholic acid (Wu et al, 2021). These acids could activate the adipose G-protein-coupled bile acid receptor and upregulate the expression of UCP1 and CKMT2, increasing heat production in white adipose tissue (Haddish and Yun, 2023). Clostridium butyricum CCFM1299 could reduce obesity by increasing energy expenditure and regulating host bile acid metabolism (Liao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%